Cerai Gugat Verstek di Pengadilan Agama Surabaya Perspektif Maslahah Daruriyah - Midun, Ahmidi (Berasan: Journal of Islamic Civil Law, 2024)
The purpose of this study is to see how Islamic law is viewed if a wife wants to give up marriage for reasons that threaten her body and soul, which is reviewed from the perspective of Maslahah Daruriyah. Divorce is an attempt to release a marriage bond caused by disharmony in the household of both parties or husband and wife. One of the two types of divorce is a lawsuit divorce, in which the wife makes a claim for the right to the court to release the marriage bond. One of them happened in the decision of the Surabaya Religious Court, where one of the reasons for the objector was irresponsible husband, domestic violence and selfishness. The results of this study show that, the divorce that occurred in the Surabaya religious court if it is associated with the theory of Maslahah, then it is included in Maslahah Daruriyah, because if this divorce is not fulfilled or not carried out, it will result in damage and disability in the human being, so it is necessary to divorce as a way to meet the primary needs of human beings and achieve benefits. This research uses the normative juridical method, which is carried out to identify the concepts, principles and principles of sharia related to divorce lawsuits.